2017
DOI: 10.1007/s10286-017-0463-1
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary autonomic dysfunction in patients with ANCA-associated vasculitis

Abstract: Patients with AAV exhibit parasympathetic pupillary autonomic dysfunction. Although correlations were weak and not significant, pupillary autonomic dysfunction is rather linked to chronic damage than to active inflammation or symptoms of autonomic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The pupillary light reflex (PLR) is regulated by the cholinergic system, which mediates pupillary constriction to light stimulation [6]; therefore, quantitative measurement of the pupillary function with automated infrared pupillometry represents an attractive tool for evaluating cholinergic activity in the clinical setting [14][15][16][17][18] and is emerging as a novel monitoring and diagnostic tool in neurological conditions (e.g., Alzheimer's and Parkinson's disease) in which cholinergic deficit is implicated in disease pathogenesis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The pupillary light reflex (PLR) is regulated by the cholinergic system, which mediates pupillary constriction to light stimulation [6]; therefore, quantitative measurement of the pupillary function with automated infrared pupillometry represents an attractive tool for evaluating cholinergic activity in the clinical setting [14][15][16][17][18] and is emerging as a novel monitoring and diagnostic tool in neurological conditions (e.g., Alzheimer's and Parkinson's disease) in which cholinergic deficit is implicated in disease pathogenesis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The following parameters were measured with automatic pupillometry system: pupil diameter before and after light stimulus; latency, duration, velocity and amplitude of pupillary constriction; velocity, latency and duration of pupillary dilatation. Amplitude and maximum constriction velocity re ect the active parasympathetic part of the light re ex, whereas the dilatation velocity re ects the active sympathetic part (4) In this study, all static PDs including the scotopic, mesopic low and high photopic PDs were smaller in patient group. Furthermore, the present study found that patients had higher resting PDs than healthy group.…”
Section: Resultsmentioning
confidence: 49%
“…The pupillary light reflex (PLR) is regulated by the cholinergic system, which mediates pupillary constriction to light stimulation [6], therefore quantitative measurement of the pupillary function with automated infrared pupillometry represents an attractive tool for evaluating cholinergic activity in the clinical setting [14][15][16][17][18] and is emerging as a novel monitoring and diagnostic tool in neurological conditions (e.g. Alzheimer's and Parkinson's disease) in which cholinergic deficit is implicated in disease pathogenesis [19][20][21].…”
Section: Introductionmentioning
confidence: 99%